COMPARISON OF METFORMIN AND ORAL CONTRACEPTIVE PILLS IN THE TREATMENT OF POLYCYSTIC OVARIAN SYNDROME - Mushtaq, Rabia; Iqbal, Sadaf; Abbas, Afroza; Iftikhar, Bushra; Ahmed, Waqas; Afsheen, Afeera (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare metformin and oral contraceptive pills in terms of mean change of serum testosterone levels and body mass index in polycystic ovarian syndrome. Study Design: Quasi experimental study. Place and Duration of Study: Department of Gynecology and Obstetrics, Sargodha Medical College, Sargodha Pakistan, from Apr to Dec 2019. Methodology: A total of 64 patients presenting with polycystic ovarian syndrome between 15-35 years were included. All patients were divided into two groups i.e. group 1 received oral contraceptive pills, and group 2 received metformin. Patients were clinically evaluated at baseline and 6 months after initial presentation to address the primary aim of evaluating the change in mean serum testosterone levels and body mass index after treatment. Results: The mean age of patients was 20.30 ± 4.92 years. The mean body mass index of patients at presentation was 30.32 ± 2.66 kg/m2. The mean reduction in the level of testosterone in group 1 was 5.14 ± 0.35ng/ml while in group 2 it was 2.58 ± 0.41 ng/ml (p˂ 0.001) which was statistically significant. Mean decrease in body mass index in group 1 was 1.51 ± 0.71 kg/m2 while in group 2 was 1.29 ± 0.46 kg/m2 (p=0.148) which was statistically insignificant. Conclusion: Oral contraceptive pills were better than metformin in terms of mean decrease in serum testosterone levels in women presenting with polycystic ovarian syndrome while the mean reduction in body mass index in both the groups was similar.